Description of a new species of Dixella from a cloud forest in Tlanchinol, Hidalgo and first record of Dixella aliciae (Johannsen) in Mexico (Diptera: Dixidae) - Huerta, Herón; Ibáñez-Bernal, Sergio (Zootaxa, 2023)
We present the first record of Dixella aliciae (Johannsen) in Mexico, collected in the locality of Lagunas de Zempoala National Park, Morelos state. Additionally, a new species of the genus Dixella Dyar & Shannon, Dixella machiotla sp. nov., is described and illustrated; specimens were collected in a cloud forest at an altitude of 1750 meters, in the Municipality of Tlanchinol, Hidalgo state. This new species is characterized by the shape of the gonostylus, with its distinctive digitiform mesially directed process, and dark brown katepisternum, with a small pale spot in the middle of the posterior margin.